2021
DOI: 10.3390/molecules26175409
|View full text |Cite
|
Sign up to set email alerts
|

2-IPMA Ameliorates PM2.5-Induced Inflammation by Promoting Primary Ciliogenesis in RPE Cells

Abstract: Primary cilia mediate the interactions between cells and external stresses. Thus, dysregulation of primary cilia is implicated in various ciliopathies, e.g., degeneration of the retina caused by dysregulation of the photoreceptor primary cilium. Particulate matter (PM) can cause epithelium injury and endothelial dysfunction by increasing oxidative stress and inflammatory responses. Previously, we showed that PM disrupts the formation of primary cilia in retinal pigment epithelium (RPE) cells. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…In order to identify novel metabolites that induce primary ciliogenesis, we previously developed a cell-based screening system using RPE cells. By using this screening system, we have identified several candidates for regulating ciliogenesis by screening a library of fecal metabolites [ 15 ]. Among these candidates, we have identified both L-carnitine and acetyl-L-carnitine as inducers of primary ciliogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to identify novel metabolites that induce primary ciliogenesis, we previously developed a cell-based screening system using RPE cells. By using this screening system, we have identified several candidates for regulating ciliogenesis by screening a library of fecal metabolites [ 15 ]. Among these candidates, we have identified both L-carnitine and acetyl-L-carnitine as inducers of primary ciliogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used human telomerase-immortalized RPE cells and RPE/Smo-GFP cells that stably expressed Smo-GFP proteins, as previously described [ 15 ]. The SH-SY5Y neuroblastoma cells were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed that 2-IPMA reduces oxidative stress by inhibition of excessive ROS generation by PM2.5 [22]. In addition, it was reported that 3-IPMA has free radical scavenging activity [16].…”
Section: Discussionmentioning
confidence: 98%
“…From a cell-based high content screening with a metabolite library, we identified 2-IPMA as a strong inducer for primary ciliogenesis [22]. 2-IPMA is an intermediate metabolite in leucine biosynthesis, synthesized from α-ketoisovalerate and acetyl-coenzyme A, a reaction catalyzed by 2-isopropylmalate synthase in mitochondria and exported into the cytosol [23].…”
Section: Discussionmentioning
confidence: 99%